The Prudhoe Cognitive Function Test, a scale to assess cognitive function in adults with Down's syndrome: inter-rater and test-retest reliability. - Margallo-Lana ML; Moore PB; Tyrer SP; Dawson H; Jenkins K; Kay DWK (Journal of Intellectual Disability Research, 2003)
BACKGROUND: The Prudhoe Cognitive Function Test (PCFT) was designed to measure cognitive function in subjects with all degrees of intellectual disability (ID) and to be administered by non-specialist raters. The aim of the present study was to measure the test-retest and inter-rater reliability of the PCFT. METHODS: Three raters, one a specialist and two non-specialists, administered the PCFT to 14 subjects with Down's syndrome on two occasions separated by 4 weeks. RESULTS: The intra-class correlation coefficients (ICCs) between the rater pairs (n=3) were 0.99, 0.99 and 0.98 (P<0.01). Floor effects were recorded for two items. The ICC for test-retest reliability was 0.99 (P<0.01). CONCLUSIONS: The PCFT is a highly reliable instrument when used by either specialist or non-specialist raters. It has excellent temporal stability.